Effect of Propane and NaCl-SDS Solution on Nucleation Process of Mine Gas Hydrate - Qiang Zhang; Qiang Wu; Hui Zhang (Journal of Chemistry)
In order to explore the method of accelerating hydration separation process to recover methane from mine gas, propane hydrate phase equilibrium was used to measure the equilibrium points of three kinds of mine gas in NaCl solution. Driving force was set as 1 MPa on this basis and high-pressure experimental apparatus of mine gas hydrate was used to carry out the nucleation kinetics experiments of mine gas hydrate for three gas samples in different concentrations of sodium chloride (NaCl) and sodium dodecyl sulfate (SDS) compound systems, which was to study the effect of propane and NaCl-SDS solution on nucleation process of mine gas hydrate. The results showed that induction time of multicomponent mine gas hydrate formation was shortened with the decrease of methane concentration and increase of propane concentration. The induction time of mine gas hydrate formation was shortened with the reduction of NaCl concentration and the increase of SDS concentration. It was found that methane and propane in multicomponent mine gas nucleated collaboratively, which simplified its nucleation process compared with the single component. NaCl has two kinds of functions.